A soy protein composite gel electrolyte with low hysteresis, low temperature resistance and fatigue resistance and preparation method thereof
Through the polymerization and salting out of soy protein and acrylamide, a biphasic structure hydrogel with chain tangles and soy protein clusters is formed, which solves the problem of poor mechanical properties of bio-based hydrogel materials and achieves low hysteresis and resistance Low temperature and fatigue resistance have promoted the industrialization of solid-state energy storage technology.
Patent Information
- Application Number
- CN202410228257.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-29
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-02-29
AI Technical Summary
The existing bio-based hydrogel materials have complex preparation processes and poor mechanical properties, which lead to limited application scope. In particular, the hydrogels produced by soy protein have poor mechanical properties.
Soy protein and acrylamide are mixed and reacted, and crosslinking agents are added to polymerize to form a polyacrylamide hydrogel with a chain tangled structure. The soy protein nanoparticle group is formed through hydrophobic association of NH4+ and SO42-. The cluster is finally immersed in zinc chloride and lithium chloride salt solutions to obtain a low-hysteresis, low-temperature and fatigue-resistant soy protein composite gel electrolyte.
A duplex structure hydrogel with low hysteresis, low temperature and fatigue resistance is achieved, which improves the toughness and fatigue resistance of the gel, improves the low temperature performance, and promotes the industrialization of solid energy storage technology.
Smart Images

Figure CN118290771B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of bio-based hydrogels, specifically relating to a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance, and fatigue strength, and its preparation method. Background Technology
[0002] Ordinary network hydrogels are three-dimensional network structures formed through physical or chemical cross-linking. They are insoluble in water but possess high swelling properties. Due to their unique physical and chemical properties, hydrogel materials are widely used in daily necessities, environmental engineering, food engineering, electronic devices, and biomedicine. Currently, a series of bio-based hydrogels have been prepared using biomass resources such as cellulose, lignin, starch, and chitosan. However, these methods suffer from drawbacks such as complex preparation processes, poor mechanical properties, and susceptibility to breakage, thus limiting their application scope.
[0003] Soy protein, as the most abundant agricultural and forestry biomass resource, has the characteristics of being renewable, abundant in reserves, biodegradable, and environmentally friendly. Because its molecular chain contains functional groups such as amino, carboxyl, hydroxyl, and thiol groups, it can react chemically with many substances. Modified soybean protein has functional properties such as solubility, water absorption and retention, gelling, emulsification, and foaming.
[0004] However, currently, hydrogels made solely from soybean protein have relatively poor mechanical properties. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0006] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0007] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance, and fatigue strength.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a method for preparing a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance, and fatigue strength resistance, comprising,
[0009] Soy protein dispersion is obtained by heating an aqueous solution of soybean protein.
[0010] Soy protein dispersion and acrylamide were mixed and reacted to obtain a precursor;
[0011] A very small amount of crosslinking agent and initiator are added to the prepolymer, and the polymer is heated to obtain a polyacrylamide polymer phase with a chain entanglement structure.
[0012] Then, the gel matrix was immersed in ammonium sulfate solution, using NH4+. + and SO4 2- The hydrophobic association with protein macromolecules promotes the "salting out" of soybean protein nanoparticles, which aggregate under the hydrophobic effect of their own long carbon chains to form soybean protein cluster phase, and then phase separation to form soybean protein-polyacrylamide hydrogel with a biphase structure.
[0013] Finally, it is immersed in a solution of zinc chloride and lithium chloride to introduce a composite salt, resulting in a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance, and fatigue resistance.
[0014] In a preferred embodiment of the preparation method described in this invention, the concentration of the soybean protein dispersion is 0.1 wt.% to 12 wt.%.
[0015] In a preferred embodiment of the preparation method described in this invention, the soybean protein dispersion and acrylamide are mixed and dissolved, wherein the molar ratio of soybean protein dispersion to acrylamide monomer is 1:2, the dissolution temperature is 40-45℃, and the dissolution time is 2-3 hours.
[0016] In a preferred embodiment of the preparation method described in this invention, the pH value of the precursor is 5 to 7.
[0017] In a preferred embodiment of the preparation method described in this invention, the crosslinking agent is N,N'-methylenebisacrylamide, and the molar ratio of the crosslinking agent to the acrylamide monomer is 3.2 × 10⁻⁶. -5 :1.
[0018] In a preferred embodiment of the preparation method described in this invention, the initiator is ammonium persulfate, and the molar ratio of the initiator to the acrylamide monomer is 1.28 × 10⁻⁶. -4 :1.
[0019] In a preferred embodiment of the preparation method described in this invention, the heating reaction yields a soybean protein composite hydrogel, wherein the heating temperature is 50–60°C and the gelation time is 2–3 h.
[0020] In a preferred embodiment of the preparation method described in this invention, the concentration of the ammonium sulfate solution is 30 wt.%, and the immersion time in the ammonium sulfate solution is 10–12 h.
[0021] As a preferred embodiment of the preparation method described in this invention, the zinc chloride and lithium chloride solution has a concentration ratio of 2-3:8 mol / kg.
[0022] Another objective of this invention is to overcome the shortcomings of the prior art and provide a method for preparing a hydrogel using a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance, and fatigue strength. The hydrogel has a water content of 75 wt.%–80 wt.%, maintains energy dissipation below 5% at both room temperature and low temperature, and achieves a tear energy of 4512 J / m at room temperature. 2 Tensile stress up to 365 kPa; tear energy at low temperature reaches 5326 J / m 2 The tensile stress was 354 kPa.
[0023] Beneficial effects of this invention:
[0024] (1) This invention provides a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance, and fatigue strength, and its preparation method. The gel electrolyte has a two-phase structure, wherein chain-entangled polyacrylamide is used as the continuous phase and soybean protein clusters are embedded therein as the dispersed phase. In the two-phase structure of soybean protein-polyacrylamide, energy is dissipated by the low sliding friction between the entangled chains, resulting in low hysteresis. At the same time, the soybean protein clusters are used to transfer stress inside the polymer, thereby achieving high toughness under low hysteresis. Furthermore, through the synergistic effect of chain entanglement and soybean protein clusters, the fatigue threshold is expanded and the fatigue strength is improved. Meanwhile, the introduced lithium chloride and zinc chloride composite salts destroy the hydrogen bonding between the solvent water, forming a solvation configuration, thereby inhibiting the freezing of the solvent water and improving the low temperature resistance of the gel.
[0025] (2) This invention introduces a phase separation structure into soybean protein hydrogel, which has excellent high toughness, high elasticity and fatigue strength. By adjusting the structure of the electrolyte, it helps to solve the problem of poor interfacial compatibility between solid electrolyte and electrode, promotes its successful application in low temperature solid energy storage system, and accelerates the industrialization process of solid energy storage technology from laboratory to production line to market.
[0026] (3) Compared with the traditional hydrogel preparation method, the preparation process of this invention is simple, the preparation conditions are mild, and no complicated post-processing procedures are required, which is conducive to the further application and promotion of solid-state energy storage technology. Attached Figure Description
[0027] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:
[0028] Figure 1 The image shows the microstructure of the soybean protein composite gel electrolyte prepared in Example 2 of this invention. a is a three-dimensional tomographic image of the gel, b and c are scanning electron microscope and elemental distribution diagrams of the gel, and d is an atomic force microscope image of the gel.
[0029] Figure 2 This is a scanning electron microscope image of the soybean protein composite gel electrolyte prepared in an embodiment of the present invention.
[0030] Figure 3 The figures show the stress-strain curves and tear energy diagrams of the soybean protein composite gel electrolytes prepared in Examples 1-4 of this invention at room temperature. In this figure, a is the stress-strain curve of the prepared soybean protein composite gel electrolyte at room temperature, and b is a comparison of the tear energy of the prepared soybean protein composite gel electrolyte at room temperature.
[0031] Figure 4 The figures show the stress-strain curves and tear energy diagrams of the soybean protein composite gel electrolyte prepared in this embodiment of the invention at low temperatures, where a is the stress-strain curve of the prepared soybean protein composite gel electrolyte at low temperatures, and b is a comparison of the tear energy of the prepared soybean protein composite gel electrolyte at low temperatures.
[0032] Figure 5 The figures show the single-stretch-release cyclic stress-strain curves of the soybean protein composite gel electrolytes prepared in Examples 1-4 of this invention at different strains at room temperature.
[0033] Figure 6 The figures show the single tensile-release cyclic stress-strain curves of the soybean protein composite gel electrolyte prepared in Examples 1-4 of this invention at different strains under low temperature.
[0034] Figure 7 The diagram shows the energy dissipation and energy dissipation coefficient of the soybean protein composite gel electrolyte prepared in Examples 1-4 of this invention at room temperature and low temperature. In this diagram, a is the energy dissipation and energy dissipation coefficient of the prepared soybean protein composite gel electrolyte at room temperature, and b is the energy dissipation and energy dissipation coefficient of the prepared soybean protein composite gel electrolyte at low temperature.
[0035] Figure 8The stress-strain curves of the soybean protein composite gel electrolyte prepared in Example 2 of the present invention under tensile release cycles at a strain of 100% are shown in Figure a; a is the stress-strain curve for every 1000 tensile cycles, and b is a summary graph of stress retention rate, plastic deformation rate and resilience for every 1000 cycles out of 10000 cycles.
[0036] Figure 9 The tensile stress-strain diagrams at room temperature are shown for the soybean protein composite gel electrolytes prepared in Comparative Example 1 and Example 2 of this invention, whether or not they have been soaked in a 30wt% ammonium sulfate solution. Detailed Implementation
[0037] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0038] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0040] Example 1
[0041] Preparation of polyacrylamide composite conductive hydrogel:
[0042] (1) Add 60g of acrylamide monomer to 30g of deionized water, stir at 45℃ for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to fully dissolve it;
[0043] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 55°C for 3 hours to obtain polyacrylamide hydrogel;
[0044] (3) Remove the sample and immerse it in a 30 wt% ammonium sulfate solution for 12 hours. Then remove it and immerse it again in a mixed salt solution of zinc chloride (3 mol / kg) and lithium chloride (8 mol / kg) for 24–48 hours until mass equilibrium is reached, yielding a soybean protein-polyacrylamide composite conductive hydrogel. Its microstructure is as follows: Figure 2 (a).
[0045] Example 2
[0046] Preparation of soybean protein-polyacrylamide composite conductive hydrogel:
[0047] (1) Add 0.9 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0048] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0049] (3) Remove the sample and immerse it in a 30 wt% ammonium sulfate solution for 12 hours. Then remove it and immerse it again in a mixed salt solution of zinc chloride (3 mol / kg) and lithium chloride (8 mol / kg) for 24–48 hours until mass equilibrium is reached, yielding a soybean protein-polyacrylamide composite conductive hydrogel. Its microstructure is as follows: Figure 2 (b) and Figure 1 The three-dimensional tomographic and atomic force micrographs of (a, d) clearly show that they are phase-separated structures.
[0050] Example 3
[0051] Preparation of soybean protein-polyacrylamide composite conductive hydrogel:
[0052] (1) Add 1.8 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0053] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0054] (3) Remove the sample and immerse it in a 30 wt% ammonium sulfate solution for 12 hours. Then remove it and immerse it again in a mixed salt solution of zinc chloride (3 mol / kg) and lithium chloride (8 mol / kg) for 24–48 hours until mass equilibrium is reached, yielding a soybean protein-polyacrylamide composite conductive hydrogel. Its microstructure is as follows: Figure 2 (c)
[0055] Example 4
[0056] Preparation of soybean protein-polyacrylamide composite conductive hydrogel:
[0057] (1) Add 2.7 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0058] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0059] (3) Remove the sample and immerse it in a 30 wt% ammonium sulfate solution for 12 hours. Then remove it and immerse it again in a mixed salt solution of zinc chloride (3 mol / kg) and lithium chloride (8 mol / kg) for 24–48 hours until mass equilibrium is reached, yielding a soybean protein-polyacrylamide composite conductive hydrogel. Its microstructure is as follows: Figure 2 (d)
[0060] Example 5
[0061] Mechanical property testing of soybean protein-polyacrylamide composite conductive hydrogel:
[0062] The mechanical properties of the soybean protein-polyacrylamide composite conductive hydrogel were tested at room temperature (25°C) using a universal testing machine, including tensile properties and fatigue strength.
[0063] The soybean protein-polyacrylamide composite conductive hydrogels prepared in Examples 1, 2, 3 and 4 above were made into dumbbell shapes (stretched length of 20 mm, width of 4 mm and thickness of 1.6 mm).
[0064] Then, the dumbbell-shaped sample was vertically clamped between two fixtures, and uniaxial tensile tests and single-cycle tensile-release tests under different strains were performed along the vertical direction. The tensile speed was 50 mm / min. The tensile stress-strain curve and cyclic energy dissipation diagram of the soybean protein-polyacrylamide composite conductive hydrogel were obtained. The results are as follows: Figure 3 , 5 As shown in 7(a), the soybean protein-polyacrylamide composite conductive hydrogels in Examples 2 to 4 have significantly improved strength and toughness due to the Hofmeister effect and chain entanglement structure of soybean protein.
[0065] Example 6
[0066] Mechanical property testing of soybean protein-polyacrylamide composite conductive hydrogel:
[0067] The mechanical properties of soybean protein-polyacrylamide composite conductive hydrogel at low temperature (-20℃) were tested using a universal testing machine and a high and low temperature chamber.
[0068] The soybean protein-polyacrylamide composite conductive hydrogels prepared in Examples 1, 2, 3, and 4 were formed into dumbbell shapes (stretched length 20 mm, width 4 mm, and thickness 1.6 mm). The dumbbell-shaped samples were then vertically clamped between two fixtures, and uniaxial tensile tests and single-cycle tensile-release tests under different strains were performed along the vertical direction. The tensile speed was 50 mm / min. The tensile stress-strain curves and cyclic energy dissipation diagrams of the soybean protein-polyacrylamide composite conductive hydrogels were obtained. The results are as follows: Figure 4 , 6 As shown in 7(b), the tensile and cycling properties of the soybean protein-polyacrylamide composite conductive hydrogels in Examples 2-4 at low temperatures can be seen. Among them, the energy dissipation in Example 2 is still very small during cycling. It can be concluded that at low temperatures, the strength and toughness of the hydrogel are greatly improved due to the Hofmeister effect and the addition of salt. Figure 8 The fatigue resistance test at low temperature of Example 2 shows that after 10,000 cycles of cyclic stretching, Example 2 still maintains low energy dissipation, high stress retention rate, low plastic deformation rate and high resilience. The high overlap of each curve indicates that the biphase structure caused by the Hofmeister effect of soybean protein can simultaneously ensure the high elasticity and high toughness of the hydrogel at room temperature.
[0069] Example 7
[0070] Electrochemical performance testing of soybean protein-polyacrylamide composite conductive hydrogel:
[0071] Conductivity tests were performed on the soybean protein-polyacrylamide composite conductive hydrogel using an electrochemical workstation.
[0072] The soybean protein-polyacrylamide composite conductive hydrogels prepared in Examples 1, 2, 3, and 4 were cut into cuboid samples with a length of 10 mm, a width of 10 mm, and a thickness of 1.6 mm to prepare Pt|composite conductive hydrogel|Pt symmetric cells. Electrochemical impedance spectroscopy was used to analyze the cells at frequencies from 0.01 to 10 ppm. 5 Hertzian measurements were used to determine the ionic conductivity of the composite conductive hydrogel.
[0073] As shown in Table 1, the soybean protein-polyacrylamide composite conductive hydrogels in Examples 2-4 demonstrate the Hofmeister effect of soybean protein and the improvement of electrochemical performance of the hydrogels by the introduction of salt.
[0074] Table 1
[0075] <![CDATA[Ionic conductivity / mScm -1 > Example 1 58.82 Example 2 68.67 Example 3 86.48 Example 4 90.90
[0076] Comparative Example 1
[0077] Preparation of soybean protein-polyacrylamide composite conductive hydrogel:
[0078] (1) Add 0.9 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0079] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0080] (3) After taking it out, it is directly immersed in a mixed salt solution of zinc chloride and lithium chloride with a concentration ratio of 3 mol / kg and 8 mol / kg for 24 to 48 hours until mass equilibrium is reached, to obtain soybean protein-polyacrylamide conductive hydrogel.
[0081] Comparative Examples 1 and 2, using the mechanical testing method of Example 5, the tensile stress-strain curves of the soybean protein-polyacrylamide composite conductive hydrogel were finally obtained, and the results are as follows. Figure 9 As shown, it can be seen that the soybean protein-polyacrylamide composite conductive hydrogel in Example 2 has a structure that is altered by the Hofmeister effect of soybean protein caused by ammonium sulfate ions, which greatly improves the strength and toughness of the hydrogel.
[0082] Comparative Example 2
[0083] (1) Add 0.9 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0084] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0085] (3) Take it out and immerse it in a 30wt% ammonium sulfate solution for 12 hours. Take it out and then immerse it in a lithium chloride solution with a concentration of 11 mol / kg for 24-48 hours until mass equilibrium is reached, and obtain soybean protein-polyacrylamide composite conductive hydrogel.
[0086] Comparative Example 3
[0087] (1) Add 0.9 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0088] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0089] (3) Take it out and immerse it in a 30wt% ammonium sulfate solution for 12 hours. Take it out and then immerse it in a zinc chloride salt solution with a concentration of 11 mol / kg for 24-48 hours until the mass balance is achieved, and obtain soybean protein-polyacrylamide composite conductive hydrogel.
[0090] Comparative Example 4
[0091] (1) Add 0.9 g of soy protein to 30 g of deionized water, heat and stir at 95°C for 4 hours to disperse it evenly; after cooling to room temperature, sonicate for 8 minutes; then add 60 g of acrylamide monomer, stir at 45°C for 40 minutes, add 0.027 mmol of N,N'-methylenebisacrylamide crosslinking agent and 0.0108 mmol of ammonium persulfate to the solution, stir at room temperature for 15 minutes to dissolve it completely;
[0092] (2) Then pour it into a glass mold with a length and width of 50 mm and a thickness of 1.5 mm, and polymerize it at 60°C for 3 hours to obtain soybean protein-polyacrylamide hydrogel;
[0093] (3) Take it out and immerse it in a 30wt% ammonium sulfate solution for 12 hours, then take it out to obtain soybean protein-polyacrylamide composite hydrogel.
[0094] The electrochemical performance testing conditions for the hydrogel were the same as in Example 7. The test results are shown in Table 2. It can be seen that the synergistic effect of zinc chloride and lithium chloride improves the electrochemical performance.
[0095] Table 2
[0096] <![CDATA[Ionic conductivity / mScm -1 > Example 2 68.67 Comparative Example 2 12.87 Comparative Example 3 5.13 Comparative Example 4 0.09
[0097] This invention introduces a biphase structure into soybean protein hydrogels through polymerization and "salting out" processes. Entangled polyacrylamide acts as the continuous phase, while soybean protein clusters are embedded within it as the dispersed phase. Energy is dissipated by the low sliding friction between the entangled chains, resulting in low hysteresis. Simultaneously, the soybean protein clusters transfer stress within the polymer, achieving high toughness under low hysteresis. Furthermore, the synergistic effect of the biphase interaction between chain entanglement and soybean protein clusters expands the fatigue threshold and enhances fatigue resistance. Meanwhile, the introduced lithium chloride and zinc chloride composite salt disrupts the hydrogen bonds between the solvent water, forming a solvation configuration that inhibits the freezing of the solvent water, improving the gel's low-temperature resistance, ultimately forming a soybean protein composite gel electrolyte. This invention introduces a phase-separated structure into the soybean protein hydrogel, simultaneously possessing excellent high toughness, high elasticity, and fatigue resistance. By adjusting the electrolyte structure, it addresses the problem of poor interfacial compatibility between solid electrolytes and electrodes, promoting its successful application in low-temperature solid-state energy storage systems and accelerating the industrialization process of solid-state energy storage technology from the laboratory to the production line and then to the market.
[0098] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the present invention.
Claims
1. A method for preparing a soybean protein composite gel electrolyte with low hysteresis, low temperature resistance and fatigue resistance, characterized in that: include, heating the soy protein aqueous solution to obtain a soy protein dispersion; The soybean protein dispersion and acrylamide are mixed and reacted to obtain a prepolymer; Adding a crosslinking agent and an initiator to the prepolymer, heating the reaction, and heating and polymerizing in the presence of the crosslinking agent and the thermal initiator to obtain a soybean protein composite hydrogel having a polyacrylamide polymer phase with a chain entanglement structure; The soybean protein composite hydrogel was immersed in ammonium sulfate solution, and NH4 + and SO4 2- The hydrophobic association with protein macromolecules promotes "salting out" of soy protein nanoparticles, which aggregate under the hydrophobic effect of their own long carbon chains to form soy protein cluster phases, and then phase separate to form soy protein-polyacrylamide hydrogel with a dual-phase structure, wherein the concentration of the ammonium sulfate solution is 30wt%; Then immersed in zinc chloride and lithium chloride salt solutions to obtain low hysteresis, low temperature resistance, and fatigue resistance soybean protein composite gel electrolyte, wherein the concentration ratio of zinc chloride and lithium chloride salt is 2-3 mol / kg:8 mol / kg.
2. The preparation method according to claim 1, characterized in that: The concentration of the soybean protein dispersion is 0.1wt.%~12wt.%.
3. The preparation method according to claim 1 or 2, characterized in that: The soy protein dispersion and acrylamide are mixed and reacted, wherein the molar ratio of the soy protein dispersion to the acrylamide monomer is 2:1, the reaction temperature is 40-45° C., and the reaction time is 2-3 hours.
4. The preparation method according to claim 1, characterized in that: The pH value of the precursor is 5-7.
5. The preparation method according to claim 1, characterized in that: The crosslinking agent is N,N'-methylenebisacrylamide, and the molar ratio of the crosslinking agent to the acrylamide monomer is 3.2×10 -5 :
1.
6. The preparation method according to claim 1, characterized in that: The initiator is ammonium persulfate, and the molar ratio of the initiator to the acrylamide monomer is 1.28×10 -4 :
1.
7. The preparation method according to claim 1, characterized in that: The heating reaction obtains a soybean protein composite hydrogel, wherein the heating temperature is 50-60° C. and the gelling time is 2-3 hours.
8. The preparation method according to claim 1, characterized in that: The immersion time in ammonium sulfate solution is 10~12h.
9. The soy protein composite gel electrolyte with low hysteresis, low temperature resistance and fatigue resistance prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The water content of the hydrogel is 75wt.%~80wt.%.
Citation Information
Patent Citations
Soybean protein composite hydrogel high in elasticity and fatigue strength, and preparation method thereof
CN110358028A
Preparation of all-solid-state super capacitor based on hydrogel electrolyte
CN110648862A
Cited By
Flexible low-temperature-resistant gel electrolyte and application thereof in aqueous battery
CN121662979A